Diseño y Construcción de un Prototipo de Mecanismo para Fabricar Estribos de Refuerzo Estructural (2020)
— This article presents the design and construction of an alternative mechanism prototype for manufacturing reinforcing steel square links. This solution seeks to replace the manual work of workers in the construction sector for operations of figuration and cutting of steel square links; which are used as reinforcement in the manufacture of concrete columns. The design and manufacturing process of the prototype is described, as well as the different types of mechanisms that can be used for dragging, bending and cutting operations. Finally, recommendations are proposed for improvement